A coexistence mechanism for two freshwater prawns in the Paraná river floodplain - Collins, Pablo Agustin (2005)
ABSTRACTThis study examined the circadian feeding cycles of two sympatric decapod prawns Palaemonetes argentinus (Nobili, 1901) and Macrobrachium borellii (Nobili, 1896) as a coexistence mechanism. The work was done in some shallow lakes of the alluvial valley of the Paraná River (Santa Fe, Argentina). Both consume similar food items, but differ in their feeding times.  Macrobrachium borellii stomach fullness was greater during night than day, whereas P. argentinus foraging activity occurred by day. Trophic niche breadth was wide and similar in both species, but was expanded in P. argentinus at night when M. borellii feeding activity increased. Niche overlap fluctuated without a definite pattern. Adaptive modifications of circadian feeding rhythms play an important role in the coexistence of these species.